Fintech Di Era Digital Untuk Meningkatkan Kinerja ZIS di Indonesia - Soeharjoto Soekapdjo; Debbie Aryani Tribudhi; Lucky Nugroho (ITB AAS INDONESIA Surakarta, 2019)
Purpose of this study is to predict trend value of collecting ZIS with fintech and non fintech. Data taken from BAZNAs from 2002-2017 and using descriptive statistics with linear trend and parabolic, inference statistic with paired sample test. Result shown that fintech trend like parabolic and non fintech like linear. There is a significant and power full correlation at ZIS revenue with fintech and non fintech. Thus, there is difference average of ZIS revenue before and after using fintech. Using SIMBA fintech will be affecting the revenue of ZIS. Average prediction of ZIS collecting funds from 2018-2025 with fintech is greater than using non fintech. Average growth of ZIS revenue with fintech is 9.98 percent and 5.78 percent with non fintech.